The problem-solving ability of fast learners (accelerated class) - Ceniza, Teresita (College of Education, University of the Philippines Diliman, 1975)
The aim of the study is to improve the achievement of fast learners in solving problems in Mathematics. An investigation was conducted to determine the factor most closely related to the problem-solving ability of the members of the Accelerated Class of the Jose Rizal Elementary School, Pasay City. Standardized tests were administered, scored and interpreted. The results show that the factor most closely related to the problem-solving ability is computational skills, followed by reading skills. It is concluded that the problem-solving ability of fast learners can be improved by initiating a program of activities designed to improve the computational and reading skills.